BRIDGING THE HEALTH DIVIDE: ACHIEVING EQUITY AND ACCESS IN KENYA'S HEALTHCARE SYSTEM - KOECH, GIDEON KIPCHEU (UoEm, 2024)
This paper provides a detailed analysis of healthcare access and equity in Kenya by providing historical context, current status, and critical disparities experienced in health services. It looks at the urban-rural divide, important court cases, healthcare infrastructure, public health, and the quest for Universal Health Coverage. Best practices emerge for Kenya through comparative analysis with countries like Rwanda, Ghana, and Thailand. These are all-inclusive policy recommendations, community engagement strategies, public-private partnerships, technological innovations, and capacity-building initiatives. The article concludes: "We envision a future where every Kenyan has access to the health care needed. We hope this vision inspires readers.
Keywords: BRIDGING THE HEALTH DIVIDE